Theorem on contingencies of hypersurfaces in Euclidean space - Ilmuradov, D.D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
An attempt is made to carry out a deeper study of the contingent characterization of arbitrary sets in euclidean space R^m+1.